The use of expressive arts in making sense of traumatic experiences - Parr, Rachel Ann (Philippine Journal of Psychology, 2015)
Traumatic experiences brought about by natural disasters may find survivors in a psychological state where rational and verbal modalities are not always readily accessible. Play and Mindfulness-Based Expressive Arts Therapy with Cognitive Reframing (PMBEAT) was used to look into the experiences of 39 survivors of Typhoon Yolanda through their individual and collective narratives. The resulting themes of fear, anxiety, grief, isolation, guilt, and responsibility were generated through the individual stories of the survivors shared in groupings based on their developmental stages. The collective themes of unity and transcendence were gleaned from the visual and verbal output expressed in the family collage activity. The theme “A New Beginning” was agreed upon by the entire group after reflecting on what represented them as a whole. The interpretations and themes used in the study were checked for reliability and accuracy using a modified “inter-rater clinical judgment and discussion consensus” model.